1951
DOI: 10.1021/ie50499a013
|View full text |Cite
|
Sign up to set email alerts
|

Bacitracin

Abstract: DURINGthe past several years the production of antibiotics has been one of the prime reasons for an amazing growth of the pharmaceutical industry. Penicillin was the forerunner of this new group of pharmaceuticals, but it was soon followed by streptomycin and such newer antibiotics as aureomycin, chloramphenicol, terramycin, and bacitracin. The tremendous increase in the production rates of penicillin and streptomycin in this country is shown by Table I. The newer antibiotics in most cases are produced primari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1952
1952
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…of aureomycin, and several preliminary tests had shown that freshly filtered spent broth did not require sterilization or even pasteurization for a successful fermentation. A continuous fermentation was carried out (1) in a 50-gallon experimental fermentation tank equipped with a ring sparger with fifty 0.0312-inch holes and a stirrer such as described by Inskeep et al (8). The tank was charged with 76 liters of spent aureomycin broth, and after the addition of 0.3% each of ammonium sulfate and monopotassium phosphate, it was sterilized at 120°C.…”
Section: Continuous Yeast Fermentationmentioning
confidence: 99%
“…of aureomycin, and several preliminary tests had shown that freshly filtered spent broth did not require sterilization or even pasteurization for a successful fermentation. A continuous fermentation was carried out (1) in a 50-gallon experimental fermentation tank equipped with a ring sparger with fifty 0.0312-inch holes and a stirrer such as described by Inskeep et al (8). The tank was charged with 76 liters of spent aureomycin broth, and after the addition of 0.3% each of ammonium sulfate and monopotassium phosphate, it was sterilized at 120°C.…”
Section: Continuous Yeast Fermentationmentioning
confidence: 99%
“…The demand for bacitracin has steadily increased because of its suitability for topical application and as an anti-biotic feed supplement. A new plant for the production of bacitracin was described in detail in a recent publication (201). The fermentation conditions for Bacillus subtilis Tracy grown in 24,000-gallon fermentors were as follows: temperature, 37°C .…”
Section: Antibioticsmentioning
confidence: 99%
“…Fifteen cubic feet of granular, active carbon of 10 to 20 or 10 to 30 mesh were recommended for every 100 cubic feet per minute of air passed through the filter. Inskeep et al (201) reported that air passed through carbon-packed towers has to be heated above the dew point in order to ensure sterility. It was contended that without heating to 40°to 70°C ., the carbon bed was eventually penetrated by airborne moisture droplets.…”
Section: Substratementioning
confidence: 99%
“…The development of industrial processes for the production of bacitracin was started after 1950, and the first process actually employed in industry was described by Inskeep et al (2). Under conditions of submerged cultivation in a medium containing soya meal and calcium gluconate, the yields of bacitracin attained with B.…”
mentioning
confidence: 99%